2021
DOI: 10.1136/bjophthalmol-2020-316218
|View full text |Cite
|
Sign up to set email alerts
|

Association of ambient air pollution with age-related macular degeneration and retinal thickness in UK Biobank

Abstract: AimTo examine the associations of air pollution with both self-reported age-related macular degeneration (AMD), and in vivo measures of retinal sublayer thicknesses.MethodsWe included 115 954 UK Biobank participants aged 40–69 years old in this cross-sectional study. Ambient air pollution measures included particulate matter, nitrogen dioxide (NO2) and nitrogen oxides (NOx). Participants with self-reported ocular conditions, high refractive error (< −6 or > +6 diopters) and poor spectral-domain optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…More research on this topic is needed. In agreement with our findings is that Chua et al 13 reported that higher levels of PM 2.5 were related to self-reported visually impairing AMD, thinner photoreceptor synaptic regions, thicker photoreceptor inner segment layer, and thinner retinal pigment epithelium. The authors did not adjust their model for other air pollutants, so we can only compare our single pollutant model to their results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More research on this topic is needed. In agreement with our findings is that Chua et al 13 reported that higher levels of PM 2.5 were related to self-reported visually impairing AMD, thinner photoreceptor synaptic regions, thicker photoreceptor inner segment layer, and thinner retinal pigment epithelium. The authors did not adjust their model for other air pollutants, so we can only compare our single pollutant model to their results.…”
Section: Discussionsupporting
confidence: 93%
“…Little epidemiological research exists examining the relationship between PM 2.5 and eye disease. Relationships have been identified between PM 2.5 and visual impairment, 10 glaucoma, 11 , 12 and AMD, 13 but the results for cataract are unclear. 14 , 15 To our knowledge, all of the existing studies have been done in east Asia or the United Kingdom with none being done in the United States or Canada.…”
mentioning
confidence: 99%
“…The results of the present study demonstrated that enzymatic activities of SOD and CAT were decreased by PM exposure, and that these effects were reversed by SFN posttreatment. These results suggest that SFN has antioxidant activity against RPE exposure to PM 2.5, which was recently identified as a risk factor for AMD (28).…”
Section: Discussionsupporting
confidence: 62%
“…Higher concentrations of PM 2.5 were associated decreased thickness of the ganglion cell-inner plexiform, inner nuclear, and outer plexiform + outer nuclear layers (27). Furthermore, greater exposure to PM 2.5 was associated with increased incidence of self-reported AMD and decreased thickness of the RPE layer (28).…”
Section: Discussionmentioning
confidence: 96%
“…Air pollution was linked to a higher risk of age related macular degeneration (AMD) in an observational study published in the British Journal of Ophthalmology that reviewed data from 115 954 UK Biobank participants 2. During the six year follow-up 1286 of the participants (just over 1%) had AMD diagnosed.…”
Section: Research Newsmentioning
confidence: 99%